A Longer Interstimulus Interval Yields Better Learning in Adults and Young Adolescents - Kjell, Katarina; Löwgren, Karolina; Rasmussen, Anders (Frontiers in Behavioral Neuroscience, 2018)
Eyeblink conditioning is one of the most popular experimental paradigms for studying the neural mechanisms underlying learning and memory. A key parameter in eyeblink conditioning is the interstimulus interval (ISI), the time between the onset of the conditional stimulus (CS) and the onset of the unconditional stimulus (US). Though previous studies have examined how the ISI affects learning there is no clear consensus concerning which ISI is most effective and different researchers use different ISIs. Importantly, the brain undergoes changes throughout life with significant cerebellar growth in adolescents, which could mean that different ISIs might be called for in children, adolescents, and adults. Moreover, the fact that animals are often trained with a shorter ISI than humans make direct comparisons problematic. In this study, we compared eyeblink conditioning in young adolescents aged 10-15 and adults using one short ISI (300ms) and one long ISI (500ms). The results demonstrate that young adolescents and adults produce a higher percentage of CRs when they are trained with a 500ms ISI compared to a 300ms ISI. The results also show that learning was better in the adults, especially for the shorter, 300ms ISI.